Pioneering era in paediatric tuberculosis: Utilization of 3D printing technology - Shubham Singh; Mohit Kumar; Deeksha Choudhary; Devesh Kumar; Dikshant; Shital Zambad; Shruti Chopra; Manjeet Bansal; Amit Bhatia (Annals of 3D Printed Medicine)
The management of paediatric tuberculosis (TB) poses substantial clinical challenges necessitating innovative approaches. The advent of 3D printing technology has ushered in a pioneering era in paediatric TB care, revolutionizing diagnostics, treatment strategies, and medical education. This abstract explores the multifaceted utilization of 3D printing in addressing these challenges. The 3D printing enables the creation of anatomically accurate models derived from patient-specific imaging data. These models aid clinicians in preoperative planning, facilitating precise surgical interventions for complicated TB cases in children. Such personalized anatomical replicas enhance surgical outcomes by allowing surgeons to simulate procedures and anticipate challenges unique to paediatric TB. Furthermore, 3D printing supports medical education by providing tangible, interactive learning tools. Complex TB pathology and treatment concepts can be visually and haptically represented through 3D printed models, enhancing understanding among healthcare professionals and students. Hands-on training with these models fosters proficiency in paediatric TB management, ensuring competent care delivery. Using 3D printing technology marks a transformative shift in paediatric TB management, offering personalized treatment modalities, enhancing surgical precision, and advancing medical education. As this technology continues to evolve, its integration into clinical practice holds promise for improving outcomes and quality of life for young TB patients globally. In this paper, the authors underscore the significant contributions of 3D printing in shaping the future of paediatric TB care, illustrating its potential to redefine standards in paediatric infectious disease management.